Reprogramming of liver metabolism during West Nile virus infection unveils novel aspects of disease pathophysiology - Patricia Mingo-Casas; Ana-Belén Blázquez; Josefina Casas; Ana Esteban; Estela Escribano-Romero; Pedro J. Sánchez-Cordón; Nereida Jiménez de Oya; Juan-Carlos Saiz; Miguel A. Martín-Acebes (Molecular Medicine)
Abstract Background West Nile virus (WNV) is a neurotropic mosquito-borne flavivirus responsible for outbreaks of encephalitis and meningitis worldwide. About 20% of infected patients exhibit abnormal liver function tests, although the participation of this organ in the pathophysiology of the disease remains unclear. To fill this gap, this study explores changes in liver metabolism during WNV infection. Methods Given the relevance of the liver as a major immune and metabolic organ, the changes in response to WNV infection were analyzed in the mouse model combining transcriptomics, lipidomics and histopathological analyses. Results Despite the absence of detectable viral replication in the liver, infection resulted in hepatic transcriptomic reprogramming that affected inflammation, immunity, biological oxidation and lipid metabolisms. Changes in the expression of genes related to glutathione metabolism, detoxification reactions, fatty acid metabolism (fatty acid oxidation and fatty acyl-CoA biosynthesis), phospholipid synthesis (phosphatidylcholine and phosphatidylethanolamine), sphingolipid synthesis, sterol metabolism and lipid droplet organization were identified. The reduction in glutathione in the liver of infected animals was confirmed and lipidomic analyses showed an increase in the content of sphingolipids, triacylglycerols and cholesteryl esters. A decrease in the cholesterol, phosphatidylcholine and phosphatidylethanolamine levels was also observed. Moreover, histopathological findings supported the development of steatosis in one-third of WNV-infected animals. Conclusions The discovery of these underestimated metabolic aspects of the infection repurposes the impact of WNV on liver function. These results will contribute to a better understanding of the physiopathology of the disease and warrant special attention to liver function during WNV infection.